2015
DOI: 10.1002/marc.201400743
|View full text |Cite
|
Sign up to set email alerts
|

Simple One-Pot Syntheses of Water-Soluble Bis(acyl)phosphane Oxide Photoinitiators and Their Application in Surfactant-Free Emulsion Polymerization

Abstract: The sodium salt of the new bis(mesitoyl)phosphinic acid (BAPO-OH) can be prepared in a very efficient one-pot synthesis. It is well soluble in water and hydrolytically stable for at least several weeks. Remarkably, it acts as an initiating agent for the surfactant-free emulsion polymerization (SFEP) of styrene to yield monodisperse, spherical nanoparticles. Time-resolved electron paramagnetic resonance (TR-EPR) and chemically induced electron polarisation (CIDEP) indicate preliminary mechanistic insights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 34 publications
0
58
0
Order By: Relevance
“…Time-resolved (TR) EPR is the method of choice for studying spin-polarized intermediates in solutions. [35][36][37][38][39][40] So far, only one paper was 3 published reporting TR EPR study in ILs. 41 Using photoexcited triplet molecule of Zntetraphenylporphyrin (ZnTPP) authors clearly demonstrated that high viscosity of ILs suppresses electron spin relaxation caused by diffusional rotation of ZnTPP.…”
Section: Introductionmentioning
confidence: 99%
“…Time-resolved (TR) EPR is the method of choice for studying spin-polarized intermediates in solutions. [35][36][37][38][39][40] So far, only one paper was 3 published reporting TR EPR study in ILs. 41 Using photoexcited triplet molecule of Zntetraphenylporphyrin (ZnTPP) authors clearly demonstrated that high viscosity of ILs suppresses electron spin relaxation caused by diffusional rotation of ZnTPP.…”
Section: Introductionmentioning
confidence: 99%
“…58-60 Toward increasing the range of wavelengths available for photopolymerizations in water, Grutzmacher and coworkers recently reported the synthesis of highly efficient, water-soluble visible light photoinitiators using monoacylphosphineoxide and bisacylphosphineoxide salts that are promising for biological applications based on their response to low doses of blue light (465 nm LED for <30 min). 61-62 In addition, cyclic benzylidene ketone-based initiators that are water soluble and responsive to two-photon near infrared light (780 nm, ∼60 to 400 mW, 100 fs pulse) may prove useful for thiol–ene photopolymerizations in biomedical applications requiring increased light penetration in situ . 63 …”
Section: Thiol–ene Reactions For Hydrogel Formationmentioning
confidence: 99%
“…[15] Fort his purpose 2 was dissolved in aqueous poly(ethylene glycol) methacrylate,which gives aclear solution (Figure 4a). [15] Fort his purpose 2 was dissolved in aqueous poly(ethylene glycol) methacrylate,which gives aclear solution (Figure 4a).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[10b, 11d,13] Furthermore,afew other copper(II) complexes were reported, and upon irradiation with light were converted into copper(I) compounds. [15] Remarkably, 1 serves as af our-electron-reducing agent and allows preparation of copper nanomaterials with high yields in aqueous systems. [15] Remarkably, 1 serves as af our-electron-reducing agent and allows preparation of copper nanomaterials with high yields in aqueous systems.…”
mentioning
confidence: 99%